Online alcohol interventions, sexual violence and intimate partner violence: A systematic review - Tait, Robert; Lenton, Simon (Elsevier, 2015)
Background - Sexual and intimate partner violence (IPV) is a leading cause of disease burden, with alcohol use strongly related to these behaviors. Online interventions have been shown to be effective in reducing both alcohol use and some alcohol-related problems. These programs are widely available especially to university students, a particularly high-risk group for sexual or IPV. Aim - We aimed to systematically review the evidence for the effectiveness of online alcohol interventions in reducing sexual violence or IPV. Methods - We searched electronic databases (PsycInfo, Embase, Global Health, Medline, CINAHI, Pubmed, and ProQuest) and hand searched key reviews. Results - From 569 titles, 23 were assessed in detail: five articles (four studies) fulfilled the inclusion criteria. All these studies were undertaken in the USA, with three recruiting college students (n = 17,332), and one using an emergency department (n = 262) sample of adolescents. We summarized the characteristics of the samples, the interventions and outcomes for alcohol use and sexual violence or IPV. Most interventions were unguided, with only one group receiving a guided intervention. Effect sizes, where they could be calculated, were small (Cohen's d < 0.2) or not significantly different to zero for alcohol, sexual violence or IPV outcomes.